First study on characterization of virulence and antibiotic resistance genes in verotoxigenic and enterotoxigenic E. coli isolated from raw milk and unpasteurized traditional cheeses in Romania - Tabaran, Alexandra; Mihaiu, Marian; Tăbăran, Flaviu; Colobatiu, Liora; Reget, Oana; Borzan, Mihai Marian; Dan, Sorin Daniel (Folia microbiologica, 2017)
The study focused on the incidence of enterotoxigenic Escherichia coli (ETEC) and verotoxigenic E. coli (VTEC) in raw milk and traditional dairy cheeses marketed in Romania, characterizing the virulence and antibiotic resistance genes of these isolates. One hundred and twenty samples of raw milk and 80 samples of unpasteurized telemy cheese were collected and cultured according to the international standard protocol. All the characteristic E. coli cultures were analyzed for the presence of STa, STb, LT, stx1, and stx2 toxicity genes. The ETEC/VTEC strains were tested for the presence of antibiotic resistance genes, such as aadA1, tetA, tetB, tetC, tetG, dfrA1, qnrA, aaC, sul1, bla SHV , bla CMY , bla TEM , and ere(A), using PCR. The results showed that 27 samples (18.62%) were positive for one of the virulence genes investigated. 48.1% (n = 13) tested positive at the genes encoding for tetracycline resistance, tetA being the most prevalent one (61.5%; n = 8). A high percent (33.3%; n = 9) revealed the beta-lactamase (bla TEM ) resistance gene, and none of the samples tested positive for bla CMY and bla SHV genes. The genes responsible for resistance to sulfonamides (sul1) and trimethoprim (dfrA1) were detected in rates of 14.8% (n = 4) and 7.4% (n = 2), respectively. E. coli is highly prevalent in raw milk and unpasteurized cheeses marketed in Romania. These strains might represent an important reservoir of resistance genes which can easily spread into other European countries, given the unique market.
Keywords: mléko; Rumunsko; Virulence Factors; bakteriální léková rezistence; genotyp; Drug Resistance, Bacterial; Genotype; polymerázová řetězová reakce; Polymerase Chain Reaction; virulence; shiga-toxigenní Escherichia coli; Microbial Sensitivity Tests; skot; bakteriální geny; Cheese; Romania; sýr; nemoci skotu; Enterotoxigenic Escherichia coli; zvířata; Gene Expression; Virulence; Shiga-Toxigenic Escherichia coli; Cattle; Escherichia coli Infections; Milk; Cattle Diseases; exprese genu; Genes, Bacterial; enterotoxigenní Escherichia coli; mikrobiální testy citlivosti; faktory virulence; infekce vyvolané Escherichia coli; Animals